Effect of Spacing Configuration and Number of Hangers on Structural Performance of Tied-Arch Bridges - Mohammad Salman Alfarisi; Fajar Tamami; Daffa Syarif Abdullah; Puput Risdanareni (Universitas Islam Raden Rahmat, Malang, 2025)
Optimized tied arch bridges offer efficient material usage in the structure. This research studied the effects of varying the spacing and number of hangers. The use of symmetrical spacing variations (X), decreased towards the middle of the span (Y), and decreased towards the end of the bridge (Z), combined with different numbers of hangers, namely 8, 10, and 12 pieces, these variations produced 9 bridge models. The objective was to find the best structural performance that minimized structural weight and deflection, thereby reducing steel usage and CO2 emissions. This study used SAP2000 v.25 for 3D model analysis, with a 250 Kg load in the middle of the span using the tributary method, which distributes the load to the longitudinal bars and transverse bars, representing the load of several pedestrians in the middle of the bridge channeled by the floor plate to the bars below. The results showed that the spacing type and number of hangers affect the structural performance. The Z spacing type produced the lowest average structural weight, while the 10 hangers gave the smallest average deflection compared to the other hangers. In conclusion, optimization was successful by combining the z-type spacing with 10 hangers.